Alternative irrigation institutions in canal command: the case of the Chalakkudy River Diversion Scheme in Kerala - Neetha, N. (International Water Management Institute, 2003)
Research highlight based on a paper titled Alternative irrigation institutions in canal-command: the case of Chalakkudy River Diversion Scheme in Kerala, South India